Effective framework of smart toilet in addressing the emotional needs of new elderly - Li, Qiuyi (2024)
With the advent of social transformation and population ageing, a unique group known as the “new elderly” has emerged. Unlike traditional elderly people, this group is significantly influenced by contemporary social structures and technological advancements, reshaping their emotional needs and expectations from products. There is a close connection between the emotions and health of the elderly, so addressing their emotional needs is essential for their overall well-being. As one of the most common daily activities, toilet usage can significantly impact their emotional state, with difficulties in this area often leading to negative emotions. Well-designed smart toilets can greatly alleviate these negative emotions. Despite their importance, the integration of various technologies into smart toilets for the elderly is often overlooked. Currently, there is no clear product design framework specifically tailored to meet the emotional needs of the new elderly regarding smart toilets. This study aims to identify the specific emotional needs of the new elderly by combining Norman’s theory on three levels of emotional design with Maslow’s hierarchy of needs theory. We conducted a survey in China yielding 501 valid responses and performed a detailed analysis to identify the emotional factors in designing products, especially smart toilets, for this demographic. Based on the comprehensive research findings, we have developed a product design framework that addresses the emotional needs of the new elderly and provided recommendations for designing smart toilets suitable for this group.